Impact of External Ankle Dorsiflexion Restriction on Sagittal Plane Kinematics and ACL Injury Risk in Big Mountain Skiers - Megan Bass; Kaelin Enga; Deirdre O'Sullivan; Dori O'Sullivan; Eryn Murphy (Undergraduate Research Journal for the Human Sciences, 2025)
Introduction. Big mountain skiing involves frequent impacts on extreme terrain and stiff boots that alter lower extremity joint kinematics consistent with ACL injury mechanisms. Back-weighted sagittal loading patterns identified in Alpine skiing, such as boot-induced anterior drawer of the tibia, remain unstudied in big mountain skiing. Purpose. This study characterizes the effect of ankle dorsiflexion restriction induced by big mountain ski boots on lower extremity sagittal joint kinematics in the context of known ACL injury mechanics. Methods. Participants completed five isometric squats under two conditions: restricted and unrestricted ankle dorsiflexion. Squat trials simulated a skier’s stance. Two-way ANOVA and paired t-tests compared restricted and unrestricted conditions. Results. Significant differences in ankle dorsiflexion and knee flexion angles were observed between conditions. Conclusion. These results indicate restrictive ski boots may alter sagittal plane kinematics in patterns consistent with ACL injury mechanisms in big mountain skiing.
Keywords: Skiing; ACL injury risk; ankle dorsiflexion restriction; sagittal plane